1991
DOI: 10.1139/l91-061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mixing on anaerobic treatment of potato-processing wastewater

Abstract: Four laboratory-scale reactors were used to study the effects of mixing intensity and mixing duration on the anaerobic treatment of potato-processing wastewater at 20 °C. The mixing intensities were set at impeller speeds of 0, 20, 50, and 100 rpm. Two mixing durations were studied: 45 and 15 min/h. It was found that both mixing intensities and mixing durations studied and their joint effect significantly affected the steady-state performance of the anaerobic reactors in treating the potato-processing wastewat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 7 publications
1
6
0
1
Order By: Relevance
“…This implies gas release may be hindered in unmixed digesters, and mixing increases the chances of mass transfer from liquid phase to gas phase. This is consistent with results of Lin and Pearce, [57] and Karim et al [22] with the conclusion that there is impact on methane production between intermittent mixing mode and unmixed systems. In addition, Stafford [58] showed that there was a gradual release of biogas from the liquid phase to the gas phase during the first minute of mixing for various intermittent mixing periods (140-1000 rpm).…”
Section: Effect Of Loading Rate Volumetric Biogas Production Vfa Cosupporting
confidence: 92%
“…This implies gas release may be hindered in unmixed digesters, and mixing increases the chances of mass transfer from liquid phase to gas phase. This is consistent with results of Lin and Pearce, [57] and Karim et al [22] with the conclusion that there is impact on methane production between intermittent mixing mode and unmixed systems. In addition, Stafford [58] showed that there was a gradual release of biogas from the liquid phase to the gas phase during the first minute of mixing for various intermittent mixing periods (140-1000 rpm).…”
Section: Effect Of Loading Rate Volumetric Biogas Production Vfa Cosupporting
confidence: 92%
“…It is therefore postulated that slow mixing helps to improve the stability and loading capacity of thermophilic digesters that treat substrates in the absence of an acclimatized seed. Similarly, Lin and Pearce [31] demonstrated that methane production was higher during intermittent mixing when compared to an unmixed digester and a study by Tian et al [32] proved that continuous mixing resulted in declined biogas production rates [32,33]. From day 15 to 31 during the minimum mixing speed of 10 rpm, lower biogas production was observed due to higher VFAs concentration and instabilities in the AD process.…”
Section: Effect Of Mixing Intensity On Biogas Production Ratementioning
confidence: 92%
“…It is therefore postulated that slow mixing helps to improve the stability and loading capacity of thermophilic digesters that treat substrates in the absence of an acclimatized seed. Similarly, Lin and Pearce [31] demonstrated that methane production was higher during intermittent mixing when compared to an unmixed digester and a study by Tian The volume-averaged velocity magnitudes were obtained as (Equation ( 5)):…”
Section: Effect Of Mixing Intensity On Biogas Production Ratementioning
confidence: 99%
See 1 more Smart Citation
“…From the intensive literature review, it was observed that the approach to studying mixing efficiency depends on the scale of the biogas digester. For instance, in the lab-scale experiments, the general focus is on the determination of the amount of biogas production rate [19,64], methane content [65,66], the behavior of microorganisms [36,67,68] and dead zones [27,51] by varying the rotational speed of the impeller. Each factor has its own significance and importance.…”
Section: Parameters For Evaluation Of Mixing In Anaerobic Digestermentioning
confidence: 99%